Cannabis and tobacco smoke are not equally carcinogenic - Melamede Robert (BMC, 2005)
Abstract More people are using the cannabis plant as modern basic and clinical science reaffirms and extends its medicinal uses. Concomitantly, concern and opposition to smoked medicine has occurred, in part due to the known carcinogenic consequences of smoking tobacco. Are these reactions justified? While chemically very similar, there are fundamental differences in the pharmacological properties between cannabis and tobacco smoke. Cannabis smoke contains cannabinoids whereas tobacco smoke contains nicotine. Available scientific data, that examines the carcinogenic properties of inhaling smoke and its biological consequences, suggests reasons why tobacco smoke, but not cannabis smoke, may result in lung cancer.